THE EFFECT OF CELEBRITY ENDORSER AND PRICES ON THE JGLOW PRODUCT PURCHASE DECISION PROCESS - Yudhi Koesworodjati; Meita Sapira (Jurnal Riset Bisnis dan Manajemen, 2023)
This research was conducted based on data on the increasing contribution of the creative industry sub-sector of Bandung City to PDRB in 2018 to 2020. The research method used is descriptive and verification method with a total sample of 100 respondents. The data analysis method used is multiple linear regression analysis, multiple correlation and coefficient of determination. The results showed that there was a positive and significant influence between celebrity endorser and price on the purchasing decision process. The magnitude of the influence of celebrity endorser and price on the purchasing decision process simultaneously is 53.4% and the remaining 46.6% is influenced by other variables not examined. Partially the magnitude of the influence of celebrity endorsers on the purchasing decision process is 9.4% and the influence of price on the purchasing decision process is 44%, so it can be concluded that the price has the greatest influence on the purchasing decision process.